Project-Based Folktale Reading Learning with a Scientific Approach for Grade IV Reviewed from the Completion of Learning Outcomes - Aidah, Rofiah Nur; Seliro Wangi, Nisaul Barokati (EDU-KATA, 2025)
Indonesian language learning requires language skills that include listening, speaking, reading, and writing. One important aspect in this learning is reading, which plays a role in improving students' understanding of the text. This study aims to analyze the results of project-based folklore reading learning with a scientific approach in grade IV students. The research method used is a descriptive qualitative method with data collection techniques through observation, documentation, and analysis of student learning outcomes. The results showed that out of 10 students who participated in the learning, 7 students (70%) achieved learning completion with a final score of ≥ 70, while 3 students (30%) had not achieved the Minimum Completion Criteria (KKM). Students with good reading comprehension tend to get higher project and presentation scores, while students with low comprehension have difficulty in both aspects. This shows a correlation between reading comprehension skills and success in project and presentation assignments. Based on these findings, more varied learning strategies are needed to help students who have not achieved completion, such as additional guidance, effective reading techniques, and more intensive presentation practice. With a more interactive and student-oriented approach, it is expected that all students can achieve optimal learning outcomes.